An Exploratory Study on the Emotions of Undergraduate Mathematics Students during the Secondary-Tertiary Transition - Yasmin Cruz Hernández; José A. Juárez-López; Alfonso Díaz-Furlong (Pendidikan Matematika STKIP Kusuma Negara, 2024)
This descriptive, qualitative research explores the evolution of emotions in students of the bachelor’s degree in mathematics and applied mathematics during the secondary-tertiary transition. It uses the Theory of the Cognitive Structure of Emotions (better known as the Ortony, Clore, and Collins's [OCC] theory) as a theoretical framework. The study was carried out at the Faculty of Physical and Mathematical Sciences of the Meritorious Autonomous University of Puebla, Mexico, with the participation of seventeen first-year students, selected by convenience sampling. Three emotions were identified, of which four were positive and nine were negative. The findings indicate that emotional experiences have a considerable effect on the ability of students to acquire advanced mathematical language. The research is based on a descriptive empirical design, focusing on the experiences of the participants. The data collection instruments include an incomplete sentence questionnaire, a questionnaire, and a semi-structured interview. The research highlights the importance of considering emotions in the secondary-tertiary transition, stating that experiences are crucial in the transition and it is essential to address these aspects to improve support for students in their mathematical learning.